ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI BERBASIS DATA PADA SISTEM PERSEDIAAN DAN PENJUALAN (STUDI KASUS PADA CV PRIMA MOTOR, BANDA ACEH) - Risky, Sheila Fathia; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The system inventory and sales is a thing that is not familiar to a company. CV Prima Motor is a company engaged in workshop (automotive). Handling data using manual systems resulting in frequent errors. In the development of the company to see the existence of stock items are still using manual systems so that it takes a very long time. Same is the case with a system inventory, sales system on the company also still use the manual system so that employees are very easy of doing the cheating. The goal of the research is to design an information system accounting-based data on inventory and sales systems in order to facilitate employees in search of stock items and reduce fraud committed by employees. Design system uses the Visual Basic 6.0 programming language and MySQL as its data base. In this study using qualitative descriptive method.The results of this research is to produce an application that can perform inventory control and sales transactions that are more informative so it can make the goods that enter or exit. Keywords: System inventory, Sales System, Visual Basic 6.0, Database